Efektifitas Edukasi Berbasis Audiovisual Tutorial tentang ARV terhadap Kepatuhan Pengobatan Pasien HIV/AIDS di Puskesmas Bandarharjo, Semarang, Provinsi Jawa Tengah - Rahayu Winarti; Niken Sukesi; Iq Ballurohman; Nanang Bagus (BADAN PENERBIT STIEPARI PRESS, 2025)
Adherence to antiretroviral (ARV) medication is a crucial factor in the success of HIV/AIDS patient therapy. Adherence levels are often low due to a lack of knowledge, motivation, and support. Audiovisual and tutorial-based education is considered capable of improving patient understanding, thereby encouraging medication adherence. This community service activity aims to provide education to HIV/AIDS patients through audiovisual and tutorial media, and to assess its effectiveness on medication adherence. This community service is an implementation using the quasi-experimental method with 36 participants from a total population of 40 people. Data were processed statistically with SPSS and using the Wilcoxon test. Evaluation was carried out through pre-tests and post-tests and was participatory during the activity. The results of the activity showed an increase in patient understanding of ARVs, as well as increased medication adherence after being given educational interventions at the Bandarharjo Community Health Center. The results of the activity carried out with audiovisual and tutorial-based educational media showed an increase in knowledge of 92% of 36 patients after being given audiovisual and tutorial education, Medication Adherence; Before the intervention, almost 100% of patients were non-compliant with ARV medication. After the educational intervention, this increased to 92%. Patients reported feeling more motivated and understanding the material more easily through audiovisuals compared to traditional lectures. Tutorials helped them gain confidence in managing their medication schedules. Based on the analysis using the Wilcoxon test, a p-value of 0.000 indicates that the treatment or intervention significantly improved patient adherence to ARV treatment. Audiovisual and tutorial-based education has been proven effective in improving medication adherence in HIV/AIDS patients. This method can be used as an educational intervention strategy in community health centers and hospitals to improve the quality of care for HIV/AIDS patients.